PENGARUH PENGALAMAN AUDITOR DAN REMOTE AUDIT TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK (KAP) DI KOTA PADANG - Putri Selvita; Teguh Hidayat (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the influence of auditor experience and remote audit on auditor performance at a Public Accounting Firm (KAP) in Padang City. The research method used is a quantitative approach with multiple linear regression analysis. The research sample consisted of 40 auditors selected using a purposive sampling technique. The results show that auditor experience has a positive and significant effect on auditor performance, while remote audit has a negative and insignificant effect on auditor performance. This indicates that auditor experience is a major factor in improving auditor performance, while the implementation of remote audit has not provided an optimal contribution